Dowry : bridging the gap between theory and practice - Bradley, Tamsin; Tomalin, Emma; Subramaniam, Mangala (Women Unlimited, 2009)
This book explores dowry practices I in South Asia from a number of I theoretical perspectives and through a multidisciplinary lens. It provides an overview of these debates and discussions as they have developed since the 1960s, with the emergence of the Indian women's movement in particular. New research asks important questions about the spread of dowry, the shifting dynamics of the dowry terrain, and the role of gender in underpinning dowry abuse. How is the practice being resisted both in South Asia, as well as globally? What roles do religion, culture, economics, class or caste play in shaping dowry practices as well as perpetuating the abuse of dowry customs that result in death or injury to women across South Asia This volume analyses and explores the dynamics of these changes and the complexities they involve. It highlights the particular role that academic research can play and presents suggestions about the sorts of activism and action necessary to end dowry injustice.